Apocrine Cystadenoma of the Eyelid: A Rare Palpebral Neoplasm. Report of 2 Cases. Issue 2 (March 2018) - Charles, Norman C.; Patel, Payal; Belinsky, Irina; Oami, Shimon
Abstract : The authors report 2 cases of apocrine cystadenoma of the eyelid, 1 of which was studied with immunohistochemical and other special stains. While a previous report describes the tumor in a palpebro-orbital location, no other detailed descriptions of a purely eyelid location are present in the literature. Apocrine cystadenoma occupies an unusual portion of the spectrum of Moll gland tumors of the eyelid. It has no definitive clinical characteristics and may be diagnosed pathologically by hematoxylin-eosin–stained sections. Abstract : The authors describe 2 cases of apocrine cystadenoma of the eyelid, a benign neoplasm having only 1 previous report of a partial palpebral location.